Pengaruh Media Pembelajaran Berbasis Web Genially Terhadap Hasil Belajar Siswa Materi Seperti Apakah Budaya Daerahku Kelas V di SD Negeri Pertiwi Lamgarot - Raihatul Jannah; Intan Safiah; Nurmasyitah (STKIP Subang, 2026)
This study was motivated by the limited use of varied learning media, resulting in learning activities that have not been able to create an engaging and meaningful learning environment. This condition has contributed to students' low learning outcomes. This study aimed to determine the effect of Web Genially-based learning media on students' learning outcomes in the topic What Is the Culture of My Region Like? in Science and Social Studies (IPAS) for fifth-grade students at SD Negeri Pertiwi Lamgarot. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 60 students divided into an experimental class and a control class. Data were collected through pretest and posttest and analyzed using normality, homogeneity, N-Gain, and the Independent Samples t-test using SPSS version 26. The results showed that the mean posttest score of the experimental class was 80.00, which was higher than that of the control class (67.17). The average N-Gain score of the experimental class was 62.87, categorized as moderately effective, while the control class obtained an average N-Gain score of 33.87, categorized as ineffective. Furthermore, the hypothesis test yielded a significance value of 0.000 (p < 0.05), indicating that Web Genially-based learning media had a significant effect on students' learning outcomes in the topic What Is the Culture of My Region Like